Germany: 2015 Article IV Consultation-Press Release; Staff Report; and Statement by the Alternate Executive Director for Germany (IMF Staff Country Reports: Country Report No. 15 / 187, 2015)
KEY ISSUES Context: Growth is benefiting from lower energy prices and euro depreciation, and the labor market is strong. The external position remains substantially stronger than implied by medium-term fundamentals as the current account surplus reached another historical high. The fiscal position is healthy, corporate and household balance sheets are sound. Low interest rates are compounding chronically weak bank profitability and hurting life insurers' solvency. The population is aging fast despite record immigration, which will increasingly harm growth prospects after 2020. Policy priorities: Further progress is urgently needed to raise potential growth while generating beneficial spillovers to the rest of the euro area and lowering the large current account surplus: Step up investment addressing weaknesses in public infrastructure to strengthen potential output and domestic demand. To facilitate this process, put in place new institutions that enable better planning and coordination of public investment at the local level. Enhance competition to foster a more productive services sector. Reduce disincentives for women to work full time as a way to mitigate the adverse effects of an aging population on labor supply. Expand the macroprudential toolkit to better address potential future excesses in the housing sector. Ensure that life insurance companies maintain sufficient capital buffers to withstand a prolonged period of low interest rates